(untitled) (London Journal of Research In Science: Natural and Formal, 2025)
Security and privacy have emerged as paramount concerns in the evolving Internet of Things (IoT) ecosystem, where billions of interconnected devices exchange sensitive data over untrusted networks. Traditional cryptographic methods, while effective, are increasingly vulnerable to emerging computational threats, including those posed by quantum computing. This study proposes an enhanced blockchain-based framework that integrates zero-knowledge proofs (ZKPs) and post-quantum signature primitives to achieve robust, privacy-preserving authentication in IoT systems. The framework enables IoT devices to verify transactions and authenticate identities without revealing confidential information, thereby maintaining data confidentiality and integrity. By employing lattice-based and hash-based post-quantum algorithms, the system ensures resistance against quantum attacks while preserving computational efficiency for resource-constrained IoT nodes. Experimental evaluation demonstrates the feasibility of the proposed model in reducing communication overhead and enhancing trust among devices in decentralized networks. This research underscores the significance of combining zero-knowledge and post-quantum cryptography to build future-proof, privacy-preserving blockchain IoT systems capable of withstanding next-generation security threats.